Uncommon Presentation of Isolated Jejunal Lymphoma Masquerading as Crohn’s Disease - Swati Sattavan; Lalit Aggarwal; Priyadarshi Dikshit (Case Reports in Surgery)
Primary gastrointestinal lymphoma is a rare entity, commonly involving stomach, small bowel, and colorectum. The usual location for small bowel B cell lymphoma is distal ileum due to abundant lymphoid tissue. We are reporting the case of a 53-year-old lady presumptively diagnosed as Crohn’s disease on clinical and radiological grounds but histopathologically proven to be an unusual variant of isolated primary non-Hodgkin’s lymphoma.